The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1104/pp.20.00039
|View full text |Cite
|
Sign up to set email alerts
|

mGWAS Uncovers Gln-Glucosinolate Seed-Specific Interaction and its Role in Metabolic Homeostasis

Abstract: MS performed the experiments, wrote the manuscript, and processed and analyzed data, AY wrote the manuscript and carried out metabolic analysis, CB carried out genotyping experiments, YC analyzed data, VS analyzed data, SH carried out genotyping and metabolic analysis, EK performed GLS measurements, CK peformed initial gtr1/2 experiment, AL verified analytical methods and assisted with statistical aid, H N-E provided gtr1/2 mutants and initial analysis, DK provided all the GLS mutants and GLS related measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Moreover, increasing the annotation rate by computational sciences in combination with ion mobility, spectral library, stable isotope labeling, and ultra-high-resolution MS will enhance the discovery in metabolite-based genome-wide association study (mGWAS) 296,297 and illuminate the diversity of metabolites in the plant kingdom. Although the advances in genomics enable one to discover the gene clusters and to decode the plant revolution from the viewpoint of metabolisms, the information of metabolomics is essential not only to validate the gene functions but also to offer new opportunities for genome mining that meets with novel metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increasing the annotation rate by computational sciences in combination with ion mobility, spectral library, stable isotope labeling, and ultra-high-resolution MS will enhance the discovery in metabolite-based genome-wide association study (mGWAS) 296,297 and illuminate the diversity of metabolites in the plant kingdom. Although the advances in genomics enable one to discover the gene clusters and to decode the plant revolution from the viewpoint of metabolisms, the information of metabolomics is essential not only to validate the gene functions but also to offer new opportunities for genome mining that meets with novel metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…This approach could be called the proximate strategy, which has been frequently used for finding candidate genes in GWAS or QTL studies ( Monclus et al 2012 ; Geng et al 2015 ; Su et al 2017 ; Vanous et al 2018 ). Alternatively, LD analysis can be used to search candidate genes with procedures as described by ( Slaten et al 2020 ). As a comparison, we also tried this method to find candidate genes that are in LD with the significant SNP.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, nitrogen and GSLs are bidirectionally coordinated with GSLs influencing nitrogen signaling and/or responses. A metabolic genome-wide association study measuring natural variation in amino acid content within Arabidopsis seeds found that two key GSL biosynthetic loci were causally associated with the level of free glutamine in the seed (Slaten et al, 2020). One possible explanation for this GSL to nitrogen connection comes from the observation that specific GSLs can function as growth and development regulators through interactions with different mechanisms including the TOR complex that integrates nitrogen availability into complex signaling networks (Katz et al, 2020; Katz et al, 2015; Malinovsky et al, 2017; Salehin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%